Caracterización Geofísica del subsuelo de las estaciones acelerográficas de la red nacional de acelerógrafos (RENAC) ubicadas en Chimborazo y Bolívar - Abarca Zavala, Jhon Patricio (2023)
The Geophysical Institute of the National Polytechnic School (IG-EPN) has a national network of accelerographs (RENAC), which is responsible for the maximum recording of seismic events throughout the country. Therefore, this research aims to characterize the subsurface of accelerographic stations located in the provinces of Chimborazo and Bolívar. Methodologically speaking, in Geophysics, the recording of Ambient Seismic Noise (RSA) was used to obtain the H/V curve (mHVSR) using the Geopsy and Dinver software. In relation to the MASW method, which uses active sources to generate surface waves that are captured by sensors placed along a seismic line, their processing and data analysis were carried out in the same software to obtain dispersion curves (DC) in the cities of Guamote, Alausí, Guaranda, and Riobamba. With all the geophysical and geotechnical analyses carried out for the accelerograph station in Guamote, a soil column type "D" was generated with a Vs30 of 360 m/s and a fundamental frequency (f0) of 7.5 Hz. On the other hand, for the accelerograph station in Alausí, a soil column type "F" was obtained with a Vs30 of 400 m/s and a fundamental frequency (f0) of 2.05 Hz. Conversely, for the accelerograph station in Guaranda, a soil column type "F" was obtained with a range of Vs30 from 130 m/s to 240 m/s, as the MASW test was not available, in addition to a fundamental frequency (f0) of 1.06 Hz. Finally, in the city of Riobamba, a soil column type "F" and a Vs30 of 400 m/s were determined. It is also mentioned that the fundamental frequency could not be determined due to lack of reliability in the mHVSR curve. Given the limitations of each of the tests carried out, the analysis concludes with a variation of ysical and geotechnical results for each city. Therefore, it is important to delve into this study in the future with more precise techniques to achieve a better characterization of the soil column of the accelerographic stations.